Route Schedule Optimization Method of Unmanned Aerial Vehicle Implementation for Maritime Surveillance in Monitoring Trawler Activities in Kuala Kedah, Malaysia - Muhamad Syazwan Suteris; Fauziah Ab Rahman; Azman Ismail (International Journal of Supply Chain Management, 2018)
Unmanned aerial vehicle (UAV) or drone has been used worldwide nowadays and operate beyond our expectations. The potential of drone usefulness not only in the film industry or simply a leisure activity, search and rescue but also encompass various aspects of human life. Trawler activities in Malaysia are one of the problems that need to be worried. These activities harm and disrupt income of the small angler by entering the specific zone for the fishery activities. UAVs play an important role as a most effective way for maritime surveillance. The purpose of this research is to create the route optimization method of unmanned air vehicle implementation for maritime surveillance in monitoring trawler activities in Kuala Kedah. The objectives are (1) to identify the main factors that interfere with flying drone and (2) to identify the best route for routine monitoring schedule system for maritime surveillance in Kuala Kedah. The route planning of UAVs is the most critical and challenging problem of operation process conducted. An innovative maritime surveillance operation in which a boat concept collaborates with a drone monitoring of making a new variant of the traveling salesman problem (TSP) that we call the TSP with drones (TSP-D). In addition, this research applies the heuristic method to several artiï¬cial instances with different characteristics and sizes. Our numerical analysis shows that substantial savings are possible with this concept in comparison to boat-only delivery.